Addressing Challenges and Enhancing Sustainability in the Food Supply Chain Management for the Malaysian Armed Forces Based on IoT Technologies - Sallehudin, Muhammad Izzat; Hashim, Hani Kalsom; Shamsudheen, Mohd Iqbal; Razali, Mohd Norsyarizad; Omar, Nor Bahiyah (Society of Visual Informatics, 2025)
The critical nature of the food supply chain issues within the Malaysian Armed Forces necessitates careful consideration to establish a well-structured and organized sustainable food supply. The primary source of frustration arises from the contractor's failure to adhere to contractual obligations, resulting in inadequate supplies, delivery delays, and provisions that do not meet the specified requirements. These shortcomings indirectly impede the management process. The aim of this paper is to identify the relationship between delivery handling, quality control, condition of storage, food supply chain management, and contract management towards the quality of military fresh rations. It is also focusing on improving food supply chain management in MAF, especially the quality of military fresh rations. In addition, this study proposes potential solutions to address these issues, providing a clear path for improvement. The research methodology for this study will employ a qualitative approach. The primary data will be gathered via questionnaire surveys and subsequently analyzed using SPSS. Finally, the study concludes with some recommendations for future research, highlighting areas for further investigation.